MODERN METHODS FOR TREATING URINARY INCONTINENCE: LOOP OPERATIONS AND MINI-SLINGS (PART ONE) - Y. A. Kupriyanov; M. Y. Gvozdev; G. R. Kasyan; D. Y. Pushkar (Вестник урологии)
During the last century various loop operations are used in the treatment of stress urinary incontinence. Methods for treating urinary incontinence are inextricably linked with the development of urology as a science. Dominance concept of sphincter deficiency as the main cause of urinary incontinence led to the use of various muscle loops, which was considered by many authors, could carry the functional load. The last decade was marked by significant developments and achievements in the treatment of urinary incontinence in women. Data received today entitle say that, in general, the use of synthetic loops installed without tension in the middle of the urethra, to get rid of urinary incontinence significant number of patients with this medical and social problem worldwide. We can say that with the advent of SIMS and their use in the treatment of urinary incontinence, a new stage. The concept of using SIMS for implantation which the surgeon requires one incision under the middle third of the urethra, is not innovative. So Smith presented his minisling made of pig skin in 1987. First available for use SIMS became minisling TVT Secur company Gynaecare (Ethicon) in 2005. To date, there are many SIMS: TVT Secur®, MiniArc®, Ophira®, Adjust®, Solyx®, Zipper Sling®, Prosurg®, Tissue Fixation System®, Needleless®, Altis®, Just-swing®, Desara®. Many manufacturers do not stop and continue to develop new minislingi with new locking mechanisms.